Психологічний зміст емоцій у поліцейських з різним рівнем особистісно-професійної здійсненності - Пономаренко, Я. С.; Ponomarenko, Ya. S.; Пономаренко (Посохова) Яна Сергіївна (Вісник Львівського університету. Сер.: Психологічні науки. - 2022. - Вип.12. - С. 100–106, 2022)
Презентовано результати теоретичного та емпіричного вивчення психологічного змісту емоцій у професійній діяльності поліцейських. Визначено, що специфіка професії поліцейського базується на ситуаціях, котрі є негативними, травматичними й небезпечними, що позначається на їхній продуктивності та демонструє високі показники звільнень серед поліцейських. Виявлено специфіку емоційних переживань у професійній діяльності поліцейських, котрі мають низький та високий рівні особистісно-професійної здійсненності.

The article presents the results of theoretical and empirical study of the psychological content of emotions in the professional activities of police officers. The theoretical review of psychological literature has shown a wide range of scientific developments on the content of the emotional sphere, influence, importance and specificity of emotions in policing practice, within which the emotional experiences of police officers are a reflection of their professional difficulties but also successes and achievements. It is determined that the specifics of the police profession are based on situations that are negative, traumatic and dangerous, which affects the productivity of police officers and demonstrates high dismissal rates among police officers. The aim of the study was to identify the specifics of emotional experiences in the professional activities of police officers who have low and high levels of personality’s-professional fulfillmentity (PPF). The total sample size was 203 police officers. The results obtained by two methods: “Questionnaire of personality’s fulfillmentity” by O. Shtepa and “Questionnaire of professional self-fulfillment” by O. Kokun were subjected to cluster analysis, which allowed to form three groups by level of OPP: low – 68 persons, medium – 42 persons and high – 92 persons. The study involved only two groups of police officers – with low (first group) and high (second group) levels of PPF. It has been empirically proven that low-level police officers are willing to prefer positively colored emotions that provide enjoyment of work and life in general. For this group of respondents, emotions of security and comfort in the profession have a significant impact not only on the satisfaction of their personal lives, but also affect the perception of social situations and the content of psychological reactions. The indicators obtained in the first group of police officers significantly reduce their ability to be highly effective in their activities, but do not harm the well-being of the subjects. High-level police officers prefer emotions that contribute to the renewal of the resource base, which is narrowing due to the requirements of the profession, as well as emotions that optimize responses to external pressure and stress. Thus, the importance of the contribution of a high level of PPF is not only to ensure the quality of the functions performed by the police, but also the ability of police officers to enjoy and remain in their activities. Police officers of the second group are characterized by motivation and stability of goals, a clear understanding of the importance of self-improvement in the profession, loyalty to their beliefs and values, as well as subjectively significant emotions of pride in themselves and their profession.

Представлены результаты теоретического и эмпирического изучения психологического содержания эмоций в профессиональной деятельности полицейских. Определено, что специфика профессии полицейского базируется на ситуациях, которые являются негативными, травматическими и опасными, что сказывается на их производительности и показывает высокие показатели увольнений среди полицейских. Выявлена ​​специфика эмоциональных переживаний в профессиональной деятельности полицейских, обладающих низким и высоким уровнем личностно-профессиональной осуществимости.
Psychological content of emotions in police officers with different levels of personal-professional feasibility
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Юридична психологія. Legal psychology. Юридическая психология; поліцейські; police officers; полицейские; емоції; emotions; эмоции; особистісно-професійна здійсненність; personal and professional feasibility; личностно-профессиональная осуществимость; професійна діяльність; professional activity; профессиональная деятельность; емоційні переживання; emotional experiences; эмоциональные переживания; емоційна сфера; emotional sphere; эмоциональная сфера